The human protein kinase gene PKX1 on Xp22.3 displays Xp/Yp homology and is a site of chromosomal instability - Klink, Albrecht; Schiebel, Katrin; Winkelmann, Martina; Rao, Ercole; Horsthemke, Bernhard; Lüdecke, Hermann-Josef; Claussen, Uwe; Scherer, Gerd; Rappold, Gudrun (Human molecular genetics, 1995)
We have isolated a gene, PKX1, by virtue of its position within the candidate region for chondrodys plasia punctata in Xp22.3. Although data from one patient render It unlikely that PKX1 is the CDPX gene, this gene shows several interesting features. First, PKX1 appears to encode a novel type of human protein kinase that is related to the catalytic subunit of cAMP-dependent protein kinases and has striking homology to the DC2 protein kinase from Drosophila melanogaster. Second, PKX1 Is part of a family of at least four genes or pseudogenes, of which three map to the human sex chromosomes. In contrast to all other genes from the X-specific region of Xp22.3, PKX1 has a homologue on Vp rather than Yq. This is intriguing as it indicates that the single pericentric inversion event hypothesized to have occurred during primate evolution is not sufficient to explain the present XIV-homology pattern of Xp22.3. Third, we have characterized patients with different chromo somal rearrangements in Xp22.3 or Yp and show that a high proportion of these have occurred within the PKX1 locus. This suggests that the PKX1 gene, besides harbouring a previously described hot-spot for Illegitimate Xp/Yp-recombinatlon, contains addi tional sequences predisposing to chromosomal breakage events.
Gesehen am 31.03.2021